2001
DOI: 10.1007/s000130050550
|View full text |Cite
|
Sign up to set email alerts
|

Almost p -summing polynomials and multilinear mappings

Abstract: For several applications it is very useful to classify the linear or non-linear mappings by their summability properties. Absolutely summing operators and polynomials are prominent and classical examples of such setting. Here we are interested in the larger class of almost summing polynomials and we investigate their connections to other related notions of summability.Introduction. The successful theory of operator ideals has been a permanent inspiration for the study of special classes of multilinear mappings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The Theorem of Dvoretzky-Rogers for absolutely summing linear operators has natural versions for absolutely summing multilinear mappings and polynomials (see [9]). A linear Dvoretzky-Rogers Theorem for almost p-summing mappings can be found in [2,Ex 4.1] and tells us that if p > 1, then L al,p (E; E) = L(E; E) for every infinite dimensional Banach space E. In this section, we will show that we also have multilinear and polynomial versions for this result.…”
Section: A Dvoretzky-rogersmentioning
confidence: 92%
See 3 more Smart Citations
“…The Theorem of Dvoretzky-Rogers for absolutely summing linear operators has natural versions for absolutely summing multilinear mappings and polynomials (see [9]). A linear Dvoretzky-Rogers Theorem for almost p-summing mappings can be found in [2,Ex 4.1] and tells us that if p > 1, then L al,p (E; E) = L(E; E) for every infinite dimensional Banach space E. In this section, we will show that we also have multilinear and polynomial versions for this result.…”
Section: A Dvoretzky-rogersmentioning
confidence: 92%
“…In [2,Proposition 5.1] it is shown that if E is an L ∞ space then L( 2 E; K) = L al,2 ( 2 E; K). Next corollary shows that the aforementioned result is still valid for vector valued n-linear mappings, for every n 2.…”
Section: Propositionmentioning
confidence: 99%
See 2 more Smart Citations
“…and π as (U ) = inf {C | C as above}, see [3]. In analogy with the linear case in [10], see also [13,14], has introduced the concept of multiple almost summing operators.…”
Section: Kahane's Inequality and Multiple Kahane's Inequalitymentioning
confidence: 99%